PENGARUH PELATIHAN KOMUNIKASI INTERPERSONAL TERHADAP PENINGKATAN KEPUASAN KERJA KARYAWAN - , Tiara Caesaringga; , Prof. Dr. Thomas Dicky Hastjarjo ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Job satisfaction is an emotional condotion that is perceived as pleasant or unpleasant by the worker, so it can be said that job satisfaction reflects the feelings of employees towards their work. Interpersonal communication skills is one of the factors that determine job satisfaction. This experimental study aims to determine the influence of interpersonal communication training to improve job satisfaction in employees. The study involved 31 employees who were divided into two groups. The experimental group (15 subjects) received training job satisfaction and the other group (16 subjects) as a control group. Selection of subjects based on shift work to specify the subjects included in the control and experimental groups. This study uses the untreated control group design with pretest and posttest. The Tools used in this study was the interpersonal communication skills training module, job satisfaction scale, the observation sheet in the group receiving training, and training evaluation sheets. Levels of job satisfaction on employees was measured using the scale of work. Measurements were performed 1 week before and 6 weeks after the training of interpersonal communication. ANAVA mixed results, with suggests that interpersonal communication training can significantly improve employee job satisfaction (F = 86.963, p <0.01).